2019
DOI: 10.1097/md.0000000000014138
|View full text |Cite
|
Sign up to set email alerts
|

D-hole breakage of 2 angular stable locking plates for medial opening-wedge high tibial osteotomy

Abstract: An adequate stable fixation implant should be used for medial opening-wedge high tibial osteotomy (MOWHTO) to promote rapid bone healing without complications. To date, the highest fixation stability has been observed for angular stable locking plates. However, there is still little medical literature regarding breakage of these plates. The purpose of the present study was to report the results of plate breakage around D-hole with the use of both types of locking plate fixation for MOWHTO.Medical records of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Plate breakage near the D-hole was highly related to LHFs in a previous study [ 14 ], and the result was in accordance with the present FE results. A relative high-stress area appeared near the outside corner and the D-hole of the medial TomoFix plate in HTO, particularly with LHFs in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Plate breakage near the D-hole was highly related to LHFs in a previous study [ 14 ], and the result was in accordance with the present FE results. A relative high-stress area appeared near the outside corner and the D-hole of the medial TomoFix plate in HTO, particularly with LHFs in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In such a situation, placing a lateral plate directly at the fractured lateral hinge could efficiently stabilize the tibia with HTO and LHFs. Plate breakage near the D-hole was highly related to LHFs in a previous study [14], and the result was in accordance with the present FE results. A relative highstress area appeared near the outside corner and the Dhole of the medial TomoFix plate in HTO, particularly with LHFs in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lateral hinge fracture is a common postoperative complication of OWHTO [ 11 ] and has been reported to cause nonunion or loss of correction due to its unstable features [ 1 , 19 ]. Nha et al reported that plate breakage was associated with the presence of lateral cortical hinge fracture [ 20 ]. Furthermore, lateral hinge fracture is sometimes overlooked during surgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Floerkemeier et al reported favourable mid-term results with the use of TomoFix without artificial bone [ 23 ]. In contrast, Nha et al reported that artificial bone was inserted to minimise postoperative loss of correction when the osteotomy gap was more than 12 mm [ 20 ]. Takeuchi et al reported that they had prepared several artificial bones with heights of 7.5, 10, 12.5, and 15 mm to insert at the osteotomy site [ 8 ].…”
Section: Discussionmentioning
confidence: 99%